Your Questions Answered: Coronary Heart Disease - Newby David; Cockcroft John; Wilkinson Ian (Edinburgh Elsevier, 2005)
In the Q and A format of the "Your Questions Answered" series, this book provides information on Coronary heart disease (CHD). Aimed mainly at the primary care practitioner, it also addresses many questions asked about CHD by other physicians, practice and community nurses, medical students and trainees, and patients.
Keywords: Coronary heart disease; Coronary Disease; Angina Pectoris -- therapy